Making EU Foreign Policy National Preferences, European Norms and Common Policies - Thomas, Daniel C. (Palgrave Studies in International Relations, 2011)
A novel explanation of how EU member states overcome their divergent preferences to reach agreement on common foreign policies, with fourteen in-depth case studies covering diplomatic and security issues, enlargement, trade, development and environmental protection.